Going solo eaudiobook - Dahl, Roald (Listening Library, 2013)
“Roald Dahl sometimes shared a tonal kinship with Ogden Nash, and he could demonstrate a verbal inventiveness nearly Seussian…[His] stories work better in audio than in print.” – The New York Times Superb stories, daring deeds, fantastic adventures! Going Solo is the action-packed tale of Roald Dahl's exploits as a World War II pilot. Learn all about his encounters with the enemy, his worldwide travels, the life-threatening injuries he sustained in a plane accident, and the rest of his sometimes bizarre, often unnerving, and always colorful adventures. Told with the same irresistible appeal that has made Roald Dahl one of the world's best-loved writers, Going Solo brings you directly into the action and into the mind of this fascinating man.